Wife’s Right To Maintenance And Human Right: Concerns And Issues (Journal of Namibian Studies : History Politics Culture, 2022)
In the context of family law in India, maintenance refers to the legal obligation of a person to provide financial support to their spouse, children, or dependent family members. This obligation arises in situations where individuals are not able to support themselves adequately due to factors like marriage, separation, divorce, or other family-related circumstances. Maintenance is governed by various provisions in different personal laws, and  sought through legal proceedings, typically  maintenance order issued by a court. Exploring the human rights perspective on a wife's right to maintenance in the context of Indian law and society is crucial for several reasons like to evaluate whether existing legal provisions to promote gender equality and non-discrimination, to see whether maintenance laws are consistent with constitutional guarantees of equality, to ensures compliance with international conventions, to identify areas where Indian laws may need reform to align with international standards on women's rights, helps to assess the accessibility of justice for women, emphasises the importance of ensuring that women are not economically disadvantaged post-divorce or separation etc. This paper highlights historical background, legal framework of maintenance laws and their Alignment with International Standard, challenges faced by the women, gaps and shortcomings in the existing legal framework and on the basis of which some recommendations are being made in this paper.